PENGEMBANGAN MANAJEMEN ADMINISTRASI SEKOLAH PADA MADRASAH TSANAWIYAH - Siti Khofifah; Ahmad Fuad Hasyim; Muhammad Sholikhun (khidmatan, 2024)
This Community Service (PkM) activity was conducted at MTs YAKTI Tegalrejo with the primary objective of developing school administration management. The PkM addressed internal constraints faced by the madrasah, namely the low competency of administrative human resources (HR). The methodology employed was Asset-Based Community Development (ABCD), which involved asset identification (Discovery) and vision formulation (Dream). The main interventions designed (Design and Destiny) focused on two priority issues: (1) Data collection and organization of Class IX student documents (birth certificates, diplomas, SKHUN) and (2) Creation of student library identity cards. Implementation results showed that this assistance successfully established a more organized, efficient, and accountable work system. The program significantly improved the performance quality of the Administration Staff (Tata Usaha) and library services, affirming that asset-based administrative system development is an effective solution for supporting the optimization of the educational process in the madrasah.